New occurrence of Meloidogyne graminicola (Nematoda: Meloidogyninae) from rice fields in Italy: Variability and phylogenetic relationships. Issue 9 (20th September 2022) - Fanelli, Elena; Gaffuri, Francesca; Troccoli, Alberto; Sacchi, Stefano; De Luca, Francesca
Abstract: Since the first detection of Meloidogyne graminicola in Piedmont, North Italy, in 2016, further inspections for the presence of the rice root‐knot nematode were carried out in rice fields of neighboring regions, in accordance with the Italian NPPO (National Plant Protection Organization) to support the official phytosanitary measures, to enable the early detection of the rice pest, and to prevent its spread within the national territory. In 2018, surveys of rice fields in Lombardy region revealed a new occurrence of M. graminicola . In the present study, we confirmed the identification of the rice nematode in Lombardy using the ribosomal ITS region and the mitochondrial COI and COII genes. The sequences and phylogenetic analyses revealed that Lombardy M. graminicola population grouped in all trees in the main cluster containing Meloidogyne species belonging to graminis group, but always in a different subgroup compared to the Piedmont population of M. graminicola . These results clearly suggest that the two Italian populations have been recently and independently introduced and confirm that the geographic origin is not the main factor leading to M. graminicola population variability. Abstract : The manuscript concerns the molecular identification of the rice root‐knot nematode Meloidogyne graminicola, included in the EPPO Alert List, occurred in the North of Italy for the second time. The aim of this study is to characterize the population of rice nematode from Lombardy at ecological, evolutionary, and geographic origin level. Understanding the phylogenetic relationships among the different populations and above all between the two Italian populations can also help to address how these populations spread in Italy and the variability observed among them.